Does Story Telling Marketing Influence Consumer Purchase Decisions? A Case of A Classic Mocktail Made From Salak Bean Coffee - Pearl Loesye Wenas; Frans V. Rattu; Yurike S. Lewan; Fonny Sangari; Mikhael C. S. Mangolo; Jufrina Mandulangi; Benny Irwan Towoliu (Faculty of Economics and Business, University of Mataram, 2024)
Storytelling Marketing is usually used in marketing service products or tourism products for the purpose of emotionally influencing consumer decisions in buying the products sold. However, this is different from the usual products; in this case, the study aims to measure whether storytelling marketing effectively influences potential consumers to buy classic mocktail beverage products made from salak bean coffee. The data collection technique uses purposive sampling, with the target being mocktail connoisseurs. The data collection instrument used a questionnaire. While the data analysis method uses simple regression, correlation, and the coefficient of determination. The results showed that there was an influence between storytelling marketing and consumer purchasing decisions; besides that, the resulting correlation was strong, then the contribution of the storytelling factor was significant to consumer decisions in buying mocktails with the basic ingredients of snake fruit coffee